Green Financing and Sustainable Development in the Arab World - Shaheen, Yaser Ahmed (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of the research is to clarify the concept of green financing, the future of green financing in the Arab world, and how to build green financing tools capable of achieving sustainable green development. The study relied on the inferential approach after reviewing the literature and previous studies, as well as a description of the experiences of some Arab countries in the field of green finance and environmental conservation. Results of the study show that there are major challenges facing the Arab economy in the form of environmental change and the need for financing. The study confirmed that the demand for green financing will be strong in the future and that the Arab world has great potential to create a green infrastructure, The researcher recommended strengthening the legal and contractual aspects of green financing by the supervisory authorities, raising awareness among the lenders to provide financing tools adaptable to the requirements of environmentally friendly business, and providing incentives by governments to banks and lending agencies to enhance green financing, and integrate the market needs related to the green economy within education systems And vocational training.
Keywords: green financing; environment; sustainable green development; the Arab world